Immediate Removable Partial Denture For Aesthetic Anterior Maxillary Tooth Rehabilitation - Benita Aryani Hendrata; Paulus Budi Teguh (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: An anterior tooth extraction can cause aesthetic and psychological problems. An Immediate Removable Partial Denture could be the choice of aesthetic rehabilitation because is inserted immediately following the natural tooh extraction. Purpose: This paper reported the case of Immediate Removable Partial Denture for aesthetic anterior maxillary tooth rehabilitation in a 41-years old woman teacher. Case Report: A 41-years-old woman teacher wasn’t confident with her #22 tooth microdontia and malpositioned. In order to rehabilitated her aesthetic problem could be done by immediate #22 tooth extraction. Case Management: Removable Partial Denture preparation was done by removing the #22 tooth. The denture was inserted immediately after the extraction. After the denture was inserted, at the 24-hours, 3 days, 1 week, and 1 month should be evaluated to know the bone resorption process and whether the Immediate Removable Partial Denture should be relined or not.Conclusion(s): The Immediate Removable Partial Denture provides an aesthetic rehabilitation and increases the patient’s self-confidence because the patient has no edentulous period.